Metabolic fatigue in resuscitators using personal protection equipment against biological hazard - Rodríguez, Francisco Martín (Investigación y Educación en Enfermería, 2019)
Objective. To describe the effects of wearing individual protection equipment against biological hazard when performing a simulated resuscitation. Methods. Uncontrolled quasi-experimental study involving 47 volunteers chosen by random sampling stratified by sex and professional category. We determined vital signs, anthropometric parameters and baseline lactate levels; subsequently, the volunteers put on level D individual protection equipment against biological hazard and performed a simulated resuscitation for 20 minutes. After undressing and 10 minutes of rest, blood was extracted again to determine lactate levels. Metabolic fatigue was defined as a level of lactic acid above 4 mmol/L at the end of the intervention. Results. 25.5% of the participants finished the simulation with an unfavorable metabolic tolerance pattern. The variables that predict metabolic fatigue were the level of physical activity and bone mass -in a protective formand muscle mass. People with a low level of physical activity had ten times the probability of metabolic fatigue compared to those with higher levels of activity (44% versus 4.5%, respectively). Conclusion. Professionals who present a medium or high level of physical activity tolerate resuscitation tasks better with a level D individual biological protection suit in a simulated resuscitation. How to cite this article: Martín-Rodríguez F. Metabolic fatigue in resuscitators using personal protection equipment against biological hazard. Invest. Educ. Enferm. 2019; 37(2):e04